Ocena efektywności szkoleń menedżerów w organizacji międzynarodowej - Bartkowiak, Grażyna (Appraisal of international managers' trainings efficiency, 2006)
The subject of the article are training problems and their effectiveness on the example of Polish, French, British and American managers sample and their supervisors and employers being employed in trade company known all over the world. The article contains two parts: theoretical, based on the subject literature and empirical, describing the modem research carried out on Polish, French, British and American managers and their supervisors or employers. The following questions are to be answered: Is there a difference between important skills before and after training? In which types of skills can we observe the best results of training? Is there the a difference or correlation between the best results of training and personal appraisal system and the evaluations in the supervisors’ and employers’ opinions? The results gave the positive answer to the questions mentioned above.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 165-173